The impact of UN and US economic sanctions on GDP growth - Matthias Neuenkirch; Florian Neumeier (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2014)
In this paper, we empirically assess how economic sanctions imposed by the UN and the US affect the target states' GDP growth. Our sample includes 68 countries and covers the period 1976-2012. We find, first, that sanctions imposed by the UN have a statistically and economically significant influence on economic growth. On average, the imposition of UN sanctions decreases the target state's real per capita GDP growth rate by 2.3-3.5 percentage points (pp). These adverse effects last for a period of 10 years. Comprehensive UN economic sanctions, that is, embargoes affecting nearly all economic activity, trigger a reduction in GDP growth by more than 5 pp. Second, the effect of US sanctions is much smaller and less distinct. The imposition of US sanctions decreases GDP growth in the target state over a period of 7 years and, on average, by 0.5-0.9 pp.
Keywords: F43; F51; F52; F53; 330; Economic growth; economic sanctions; United Nations; United States